Reduction of Economic Disparities in Regions with Different Population Densities through the Agricultural Sector - Salsabila Kharisma Pramesti; Irham Irham; Hani Perwitasari (SOCA: Jurnal Sosial Ekonomi Pertanian, 2024)
Regions in Indonesia have relatively high economic growth, but are also accompanied with high economic inequality. In addition, population density tends to vary, so the opportunities to utilize resources by each population differ between regions. The objectives of this research are (1) to determine economic inequality in regions with high population density (Java-Bali), medium (Sumatra), and low (Maluku); and (2) to analyze the contribution of the agricultural sector in reducing this inequality. The Theil index analysis method is used to address the first objective, while the Theil index values with and without the agricultural sector are compared to address the second objective. The research results indicate that economic inequality in regions with high population density is higher than in regions with medium population density, and in regions with medium population density is higher than in regions with low population density. The research also confirms that the agricultural sector is able to reduce economic inequality in the research regions. The research findings are important as a basis for the development of the agricultural sector in order to reduce economic inequality